METODE KLASIKAL DAN INDIVIDUAL DALAM PEMBELAJARAN ILMU TASHRIF DI MADRASAH DINIYAH ANNAHDLIYAH KARANGPLOSO MALANG - R. Ahmad Nur Kholis (Jurnal Penelitian Ilmiah INTAJ, 2022)
This study aims to decribe how classical and individual learning methods are implemented in learning tashrīf at Madrasah Diniyah Annahdliyah Kepuharjo Karangploso Malang. This research is qualitative research and uses a case study research design. The qualitative data analysis technique used is Spradley's taxonomic-domain qualitative data analysis. The study concluded that the classical method appeared in learning tashrīf at Madrasah Diniyah Annahdliyah Kepuharjo Karangploso Malang in the core learning activities, namely in the following activities: (1) Reading together the previously studied material; (2) Activities of translating and adding materials; (3) The teacher reads the material that has been given with the best possible pronunciation; and (4) Students read together aloud imitating the teacher's reading; and (5) reading activities with the material that was just presented in the closing activity of the lesson. Individual learning appears in the learning of tashrīf at Madrasah Diniyah Annahdliyah in the core learning activities, namely in the form of student activities: presenting their respective memorization according to ability.